Reed-Solomon Codes over Galois Fields of Characteristic 3 for a Vlc Channel - Soto-Gomez, J (Institute of Electrical and Electronics Engineers Inc., 2020)
In this paper, we show that the Reed-Solomon codes built on a Galois field of characteristic 3, can be used in transmission through a visible light communication (VLC) channel, due to the information can be encoded using the colors red, green and blue. This allows us to efficiently use a VLC channel, since we can directly use the arithmetic of a Galois field of characteristic 3, and we avoid the conversion of non-binary to binary operations. Further, we show the results of our simulations for Reed-Solomon codes built on Galois fields of characteristic 3 and 2, in which we estimate a difference of 1.7 dB between these codes. © 2020 IEEE.